El lenguaje en los niños con parálisis cerebral - Parra Reyes, David (2014)
A child with cerebral palsy (CP) ischaracterized by the movement problemsin the spoken language practice, showingsince mild linguistic alterations to theimpossibility for spoken expression.In general, children with PC showalterations in the acquisition as well as inlanguage levels and expression movementproblems that affect the speech and voiceproduction.